Design, characterization, and application of antiviral agent screening platform - Park, Soo Hyun (Nanyang Technological University, 2020)
Emerging and reemerging viral pathogens are a major global health problem, and specific therapies and vaccines are unavailable for the vast majority of viral pathogens. Given the large number of circulating viruses, the development of effective antiviral strategies that work against multiple viruses is an urgent need. Conventional antiviral strategies inhibit the function of virus-specific components, which limits the range of susceptible viruses (“narrow-spectrum”), and drug-resistant virus strains often emerge quickly because these components are encoded within the error-prone viral genome. However, many medically important viruses possess an Achilles heel, namely a lipid envelope that surrounds virus particles and is a necessary structural component for viral infection. Strikingly, certain antiviral drugs, including specific amphipathic peptides, directly target the viral envelope and cause membrane destabilization, resulting in virus particle lysis and loss of infectivity. This novel antiviral strategy has several compelling features, including direct targeting of virus particles, efficacy against a wide range of enveloped viruses (“broad-spectrum”), and restrain the emergence of drug-resistant virus strains (because virus envelopes are obtained from the host cell membranes, not from the viral genome). However, mechanistic details about the membrane destabilization process remain to be understood, and tackling this problem requires innovative experimental strategies. Herein, the development of an antiviral peptide screening platform was reported that integrates soft matter design components together with biomaterial and surface functionalization strategies to facilitate highly parallel measurements tracking peptide-induced destabilization of nanoscale, virus-mimicking small unilamellar vesicles with tunable size and composition. The key design steps are presented, including tethering strategy, measurement concept, and data analysis, and important advantages of this single-particle tracking scheme are discussed vis-à-vis ensemble-averaging methods. To demonstrate the utility of this approach, the vesicle-rupture activity of an amphipathic, α-helical (AH) peptide, was investigated and further conducted a series of proof-of-concept experiments to optimize the screening platform. Additional experiments were conducted with complementary measurement tools in order to validate the measurement readouts. In addition, a micropatterning strategy was applied to control the spatial position of tethered vesicles, thereby establishing a method to create highly ordered vesicle assemblies. Based on the successful development of this screening platform, two most promising antiviral peptide candidates were evaluated using this platform and other multiple techniques. By establishing structure-function relationships that correlate the amino acid sequences of peptides in this family with vesicle-rupture activity profiles, this work will improve our knowledge about the design principles behind membrane-active, antiviral peptides, and lead to the identification of promising antiviral drug candidates to advance to biological evaluation. Looking forward, the measurement capabilities developed in this work will be broadly applicable to studying other classes of membrane-active agents, including small molecules, additional peptides, and enzymes, as well.